FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR - Angelia, Angelia; Santioso, Linda (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine whether there is an impact return on assets, debt to equity ratio, total assets turnover, exchange rate on stock return. This study uses population of manufacturing companies listed on the IDX in 2017-2019 period and uses purposive sampling in sample seletion, then processed with the SPSS (Statistical Package for the Social Sciences) versi 25.0 for windows. The selected samples are 175 data samples and 70 companies. The results show that return on assets have a positive and significant effect on stock return. Debt to equity ratio and total assets turnover also has a positive effect, but no significantly on stock return, meanwhile, exchange rate have a negative, but significantly on stock return.